Plasticity of Carbohydrate Transport at the Blood-Brain Barrier - McMullen, Ellen; Weiler, Astrid; Becker, Holger M.; Schirmeier, Stefanie (Frontiers in Behavioral Neuroscience, 2021)
Neuronal function is highly energy demanding, requiring efficient transport of nutrients into the central nervous system (CNS). Simultaneously the brain must be protected from the influx of unwanted solutes. Most of the energy is supplied from dietary sugars, delivered from circulation via the blood-brain barrier (BBB). Therefore, selective transporters are required to shuttle metabolites into the nervous system where they can be utilised. The Drosophila BBB is formed by perineural and subperineurial glial cells, which effectively separate the brain from the surrounding hemolymph, maintaining a constant microenvironment. We identified two previously unknown BBB transporters, MFS3 (Major Facilitator Superfamily Transporter 3), located in the perineurial glial cells, and Pippin, found in both the perineurial and subperineurial glial cells. Both transporters facilitate uptake of circulating trehalose and glucose into the BBB-forming glial cells. RNA interference-mediated knockdown of these transporters leads to pupal lethality. However, null mutants reach adulthood, although they do show reduced lifespan and activity. Here, we report that both carbohydrate transport efficiency and resulting lethality found upon loss of MFS3 or Pippin are rescued via compensatory upregulation of Tret1-1, another BBB carbohydrate transporter, in Mfs3 and pippin null mutants, while RNAi-mediated knockdown is not compensated for. This means that the compensatory mechanisms in place upon mRNA degradation following RNA interference can be vastly different from those resulting from a null mutation.